Open Architecture Framework for Integrated Virtual Product Development Systems - Angster, Scott; Jayaram, Sankar (International Journal of Virtual Reality, 1997)
In the current marketplace, products are required to proceed rapidly from conceptualization to production. This has put a great deal of pressure on the current state of computer software systems. These include computer-aided design and manufacturing systems, design for assembly systems, design for manufacture systems, and manufacturing simulation systems. Modern product development processes call for rapid designs and adapting designs to suit ever changing customer requirements. Virtual prototyping is allowing engineers to quickly create digital prototypes, allowing for quick evaluation of conceptual designs. New technologies such as virtual reality are now being used to aid engineers in the area of virtual prototyping. Existing systems using virtual reality technology are limited in their expandability, customization, or usability with current design software systems. This paper discusses an expandable and customizable architecture aimed at integrating virtual product development tools.